A phase III randomized trial comparing glucocorticoid monotherapy versus glucocorticoid and rituximab in patients with autoimmune haemolytic anaemia. (24th August 2013) - Birgens, Henrik; Frederiksen, Henrik; Hasselbalch, Hans C.; Rasmussen, Inge H.; Nielsen, Ove J.; Kjeldsen, Lars; Larsen, Herdis; Mourits‐Andersen, Torben; Plesner, Torben; Rønnov‐Jessen, Dorthe; Vestergaard, Hanne; Klausen, Tobias W.; et al.
Summary The impact of first‐line treatment with the anti‐CD 20 chimeric monoclonal antibody rituximab in patients with warm‐antibody reactive autoimmune haemolytic anaemia (WAIHA) is unknown. We report the first randomized study of 64 patients with newly diagnosed WAIHA who received prednisolone and rituximab combined (N = 32) or prednisolone monotherapy (N = 32). After 12 months, a satisfactory response was observed in 75% of the patients treated with rituximab and prednisolone but in a significantly smaller proportion (36%) of those given prednisolone alone (P = 0·003). Furthermore, relapse‐free survival was significantly better after the combined therapy than after prednisolone monotherapy (P = 0·02). After 36 months, about 70% of the patients were still in remission in the rituximab‐prednisolone group, whereas only about 45% were still in complete or partial remission in the prednisolone group. There was no significant difference between the two groups regarding adverse reactions to the studied medications. Likewise, serious adverse events were equally distributed, and no allergic reactions to rituximab were recorded. In conclusion, our data show that using rituximab and prednisolone combined rather than prednisolone alone as first‐line treatment in WAIHA increases both the rate and the duration of the response.